Civil and Military Airworthiness Recent Developments and Challenges (Volume II) - Kourousis, Kyriakos I. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Effective safety management has always been a key objective for the broader airworthiness sector. This book is focused on safety themes with implications on airworthiness management. It offers a diverse set of analyses on aircraft maintenance accidents, empirical and systematic investigations on important continuing airworthiness matters and research studies on methodologies for the risk and safety assessment in continuing and initial airworthiness. Overall, this collection of research and review papers is a valuable addition to the published literature, useful for the community of aviation professionals and researchers.